Evaluation of the Quality and Safety of Smoked Fish Produced Using a Modified Efhilink Smoking Cabinet With Different Bio-Smoke Sources - Marita Ika Joesidawati; Suwarsih Suwarsih; Sriwulan Sriwulan (Malikussaleh University, Aceh, Indonesia, 2025)
Traditional fish smoking methods often raise significant concerns regarding product safety, quality inconsistency, and environmental pollution. This study aimed to evaluate a modified Efhilink smoking cabinet designed to address these issues by utilizing agricultural waste, specifically corn cobs and coconut shells, as bio-smoke sources for producing high-quality, safe smoked fish compliant with the Indonesian National Standard (SNI 2725:2013). Three fish species (mackerel tuna, Euthynnus affinis; flying fish, Cypselurus spp.; and ray, Dasyatis spp.) were processed using the modified cabinet and a traditional cabinet (control) and subsequently analyzed for sensory properties, proximate composition, histamine, TVB-N, pH, total phenolic content, and various contaminants (microbiological, heavy metals, chemical residues, and polycyclic aromatic hydrocarbons (PAH4)). The results demonstrated that all smoked fish samples from the modified cabinet met all critical parameters of the national standard. Coconut shell smoke generally yielded superior products, characterized by higher acceptability in aroma and taste, a greater infusion of phenolic compounds (up to 0.334 mg/kg), and significantly lower levels of PAH4 contaminants compared to the traditional control. All samples from the modified cabinet exhibited histamine levels well below the 100 mg/kg safety limit (12.36–19.37 mg/kg), total plate counts within the permissible range (10 to 3.6x10? CFU/g), and a complete absence of detectable pathogens (E. coli, Salmonella spp., S. aureus, V. cholerae) or hazardous chemical residues (chloramphenicol, malachite green, nitrofuran); heavy metal contaminants were also found at levels far below the maximum allowable limits. The modified cabinet significantly outperformed the traditional method in reducing PAH4 contamination. The technology not only enhances food safety but also promotes sustainable practices by converting agricultural waste into value-added products. In conclusion, the modified Efhilink cabinet, using either corn cob or coconut shell bio-smoke, effectively produces safe, high-quality smoked fish that complies with stringent food safety standards, with coconut shells demonstrating superior performance as a smoke source by enhancing sensory attributes and bioactive compound content while minimizing hazardous contaminants.